Level of Knowledge on Stroke and Associated Factors: A Cross-Sectional Study at Primary Health Care Centers in Morocco - Ahmed Kharbach; Majdouline Obtel; Abderrahmane Achbani; Youssef Bouchriti; Kenza Hassouni; Laila Lahlou; Rachid Razine (Ubiquity Press, 2020)
Background: Stroke is increasingly becoming a major cause of disability and mortality. However, it can be prevented by raising awareness about risk factors and early health care management of patients. Objective: The aim of this study is to assess the level of knowledge on stroke, its risk factors, and warning signs in the population attending urban primary health care centers in the city of Agadir, Morocco. Methods: This is a multicentric cross-sectional study with a descriptive and analytical purpose. The study was conducted at five urban primary health care centers in Agadir in centralwest Morocco. All persons over the age of 18 years who consulted the health centers and who agreed to fill in the questionnaire were recruited, except for the foreign population and health workers. An interview questionnaire was used to assess the level of knowledge on stroke. Findings: A total of 469 participants were involved in the study. The median knowledge score was 8 (Interquartile range 4-13). High blood pressure (55.7%), depression and stress (48.8%) were the most well-known risk factors. Sudden weakness of the face, arms or legs (37.3%) was the main warning sign cited by the participants. Multivariate analysis revealed that illiteracy (OR 1.92; CI95%: 1.08-3.44) primary education (OR 3.43; CI95%: 1.63-7.21), rural residential (OR 1.67; CI95%: 1.07-2.59), no history of stroke among respondents (OR 16.41; CI95%: 4.37-61.59) and no history of stroke among relatives, acquaintances, or neighbors (OR 4.42; CI95%: 2.81-6.96), were independently associated with a lower level of knowledge of stroke (Table 4). Conclusions: The low level of knowledge on stroke among this Moroccan population indicates the importance of implementing stroke education initiatives in the community. More specifically, proximity education and awareness programs ought to be considered to anchor lifestyle preventive behaviors along with appropriate and urgent actions regarding the warning signs of stroke.